Burnout docente no trabalho com a inclusão de alunos com necessidades educacionais especiais - Barasuol, Evandir Bueno (2004)
This study is about a research of teachers background of the program of Specialization- Master s Course - Universidade Federal de Santa Maria - UFSM. It tried to identify the presence of a social phenomenon known as Burnout among 39 teachers that work with students with special educational necessities- SEN. These students are included in 9 schools of the common net of education from Três de Maio city of Rio Grande do Sul state, and they are proceeding from Hellen Keller special school. It is a research with a quantify approach using an instrument called MBI inventory- Maslach Burnout Inventory - from Maslach and Jackson, with an ED version - Educators Survey that helps to identify Burnout syndrome in teachers. It was made a theoretical research about the teachers background, the teacher identity that develops it work with SEN students and an ampler search about the origin and the ways that lead to Burnout. After the results analysis we could notice the syndrome in 21% of the teachers that participated in the research. We also noticed that 26% of these teachers are in a high level of emotional tiredness and that they are teachers of Math, Science, Geography, History, Arts, Physical Education and English subjects. These teachers are the most probable reached of Burnout. This result shows that there is an urgent necessity to revise an evaluate the process of teacher background and the importance of a less rational approach, less fragmented and more humanized for the curricula of education courses. Because of the complexity of the title, it urges to continue the present study. A deeper investigation about the feelings that pervade the teaching job with SEN students would make possible a better comprehension of their suffering and in result of this it would catch a glimpse of possibilities to intervene with strategies and resources to minimize this suffering that is affecting these professionals of education that develop their pedagogical activities in schools of the common net of education.